2005
DOI: 10.1158/1078-0432.ccr-04-1582
|View full text |Cite
|
Sign up to set email alerts
|

Myc Down-Regulation Sensitizes Melanoma Cells to Radiotherapy by Inhibiting MLH1 and MSH2 Mismatch Repair Proteins

Abstract: Purpose: Melanoma patients have a very poor prognosis with a response rate of <1% due to advanced diagnosis. This type of tumor is particularly resistant to conventional chemotherapy and radiotherapy, and the surgery remains the principal treatment for patients with localized melanoma. For this reason, there is particular interest in the melanoma biological therapy. Experimental Design: Using two p53 mutant melanoma models stably expressing an inducible c-myc antisense RNA, we have investigated whether Myc pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 50 publications
2
29
0
Order By: Relevance
“…S2). MYC downregulation has previously been shown to promote apoptosis (3,12), and given that siRNA to MYC was more toxic in H1299 cells, we determined whether apoptosis was the mode of cell death in this cell system (Fig. 4C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S2). MYC downregulation has previously been shown to promote apoptosis (3,12), and given that siRNA to MYC was more toxic in H1299 cells, we determined whether apoptosis was the mode of cell death in this cell system (Fig. 4C).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have indicated the association of MYC with the promoters of DNA double-strand break (DSB) repair genes Nbs1, Ku70, Rad51, BRCA2, Rad50, Rad54L, and DNAPKcs (8)(9)(10)(11) and the expression of mismatch repair genes (12)(13)(14). DSBs are repaired by two major pathways: homologous recombination (HR) and nonhomologous end joining (NHEJ).…”
Section: Introductionmentioning
confidence: 99%
“…MYC also regulates mismatch repair genes. For example, MYC down-regulation correlated with decreased levels of MSH2 and MLH1 in a gamma radiation-treated melanoma cell line (Bucci et al 2005). It was also observed in hypoxic conditions in multiple tumor cell lines that the promoters of MSH2 and MLH1 changed from being occupied by MYC/MAX to MAX/MAD1 and MAX/MNT complexes (Bindra and Glazer 2007;see Hurlin 2013 andConacci-Sorrell et al 2014 for a description of the MXD/MNT proteins).…”
Section: Myc and Dna Damage And Repairmentioning
confidence: 90%
“…c-Myc induces apoptosis and sensitizes cells to various apoptotic stimuli (12,15), but also has been reported to protect cells from apoptosis (6,8,10). In this study, we report that c-Myc, when it is phosphorylated and stabilized by NEMO, protects cells from IR-induced cell death.…”
Section: Discussionmentioning
confidence: 53%
“…Sensitization of non-Hodgkin's lymphoma cells to ionizing radiation by rituximab is achieved through the inhibition of c-Myc expression (9). Another study has suggested that c-Myc down-regulation sensitizes melanoma cells to radiotherapy in a p53-independent fashion by inhibiting MLH1 and MSH2 mismatch repair proteins (10). On the other hand, there have also been many reports evidencing proapoptotic function of c-Myc.…”
Section: Introductionmentioning
confidence: 99%